The Macro-dynamics of Partisan Advantage. (June 2019) - Dancey, Logan; Tarpey, Matthew; Woon, Jonathan
How do party reputations change over time? We construct a measure of the common movement in the parties' perceived policy handling abilities for the period 1980 to 2016 and investigate its relationship with the public's evaluation of Congress and the president. In contrast to key claims made in theories of congressional parties, we find an inconsistent relationship between evaluations of Congress and party reputations and find no evidence that successful agenda control enhances the majority party's reputation. Instead, our analysis shows a strong relationship between party reputations and presidential approval, reaffirming the central role the president plays in shaping party reputations.